Gendered challenges in adapting to the state policy on organic potato farming, East Khasi Hills, Meghalaya, India - Kawarazuka, Nozomi (International Potato Center, 2017)
Presented by Nozomi Kawarazuka (CIP), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.